A Comparative Prospective Study in Evaluating Candida spp. In Vitro Susceptibility through Micronaut-AM and Sensititre Yeast-One - Laura Trovato; Maddalena Calvo; Guido Scalia; Salvatore Oliveri (Microbiology Research, 2023)
Background. Among invasive fungal infection pathogens, Candida spp. represent the most common aetiological agents. The increasing rate of severe infections and the emergence of antimicrobial resistance highlight the importance of in vitro susceptibility testing. The EUCAST and the CLSI have established reference microdilutions that are reliable but difficult to apply in a laboratory routine. Commercial microdilutions could represent a valuable alternative within a diagnostic workflow. Methods. A number of 50 Candida spp. collected from positive blood samples simultaneously underwent the Sensititre Yeast-One microdilution as a standard susceptibility test and the Micronaut-AM as an experimental method. A comparison between the two techniques was produced, evaluating the effectiveness of the Micronaut-AM compared to the extensively consolidated Sensititre Yeast-One. Results. The two techniques revealed optimal agreement rates, confirming the reliability of the commercial microdilution kits within the diagnostic workflows. The results showed remarkable concordance for both susceptible and resistant isolates, highlighting slight variations in the different identified Candida species. Conclusions. Future studies about antifungal susceptibility testing should be encouraged, including molecular confirmation of possible resistance phenotypes and extended isolate numbers for the different Candida species. Moreover, it would be interesting to plan clinical trials after the execution of the examined commercial microdilution methods.